2009
DOI: 10.1074/jbc.m109.035444
|View full text |Cite
|
Sign up to set email alerts
|

The Developmentally Regulated Osteoblast Phosphodiesterase GDE3 Is Glycerophosphoinositol-specific and Modulates Cell Growth

Abstract: The glycerophosphodiester phosphodiesterase enzyme family involved in the hydrolysis of glycerophosphodiesters has been characterized in bacteria and recently identified in mammals. Here, we have characterized the activity and function of GDE3, one of the seven mammalian enzymes. GDE3 is up-regulated during osteoblast differentiation and can affect cell morphology. We show that GDE3 is a glycerophosphoinositol (GroPIns) phosphodiesterase that hydrolyzes GroPIns, producing inositol 1-phosphate and glycerol, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
61
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 27 publications
1
61
0
1
Order By: Relevance
“…As mentioned previously, recent reports have shown the remarkable characteristics of GroPIns as a water-soluble and bioactive intracellular derivative of phosphatidylinositol that is involved in a variety of cellular signaling pathways (9,19). GDE1 and GDE3 can hydrolyze GroPIns (16,18); however, the catalytic domain of these proteins is localized extracellularly and is enzymatically active in the extracellular space (13,16). These observations raise the possibility that GDE5 is a candidate for the direct regulation of the intracellular GroPIns levels.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…As mentioned previously, recent reports have shown the remarkable characteristics of GroPIns as a water-soluble and bioactive intracellular derivative of phosphatidylinositol that is involved in a variety of cellular signaling pathways (9,19). GDE1 and GDE3 can hydrolyze GroPIns (16,18); however, the catalytic domain of these proteins is localized extracellularly and is enzymatically active in the extracellular space (13,16). These observations raise the possibility that GDE5 is a candidate for the direct regulation of the intracellular GroPIns levels.…”
Section: Resultsmentioning
confidence: 53%
“…Furthermore, it is reported that GDE3 is regulated during osteoblast development and induces osteo-* This work was supported in part by a grant-in-aid for scientific research from blast differentiation and morphological changes in cultured mammalian cells (13). In addition, our recent study demonstrates that GDE3 is a GroPIns phosphodiesterase that hydrolyzes GroPIns to glycerol and inositol 1-phosphate, unlike the bacterial GP-PDEs and GDE1 (18). In mammalian cells, GroPIns is being increasingly recognized as an important intracellular messenger that is involved in various cellular signaling pathways such as cell proliferation, transformation, and differentiation (9,18,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our recent study demonstrated that GDE5 is a unique cytosolic protein that can regulate intracellular GroPCho concentration and myogenic differentiation (10). Previous work showed that both GDE1 and GDE3 can hydrolyze GroPIns (11,12) and that the biological function of GDE3 in osteoblast proliferation and differentiation appears to be mediated by GroPIns. Indeed, GroPIns has been shown to regulate cell growth in thyroid cells (4), and induction of its hydrolysis through GDE3 expression results in reduced osteoblast proliferation and the appearance of markers of osteoblast differentiation (12).…”
mentioning
confidence: 99%
“…Previous work showed that both GDE1 and GDE3 can hydrolyze GroPIns (11,12) and that the biological function of GDE3 in osteoblast proliferation and differentiation appears to be mediated by GroPIns. Indeed, GroPIns has been shown to regulate cell growth in thyroid cells (4), and induction of its hydrolysis through GDE3 expression results in reduced osteoblast proliferation and the appearance of markers of osteoblast differentiation (12). Thus, mammalian GP-PDEs have an intriguing feature; they show restricted substrate specificities, which prompted us to consider the possibility that mammalian GP-PDEs modulate GroPCho and/or GroPIns concentrations, because these intracellular GPs are increasingly recognized as bioactive molecules that are involved in a variety of cellular events (6).…”
mentioning
confidence: 99%